1997
DOI: 10.1159/000237719
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Eosinophil Cationic Protein and IL-5 in Patients with Asthma without Systemic Corticosteroids

Abstract: We measured the serum levels of eosinophil cationic protein (ECP) and interleukin-5 (IL-5) in 39 patients with asthma (symptomatic 12, asymtomatic 27) without systemic corticosteroids and 49 healthy subjects. There were significant differences in serum levels in both ECP and IL-5 between symptomatic and asymptomatic asthma, and healthy subjects. A significant positive correlation was found between serum levels of ECP and IL-5. No significant correlation was found between %FEV1 and serum level of ECP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Budesonide was given by intranasal administration (25 l each time) on Days 17,18,19, and 20 ( Figure 1). On Days 19 and 20, budesonide was given 1 h before intranasal OVA challenge.…”
Section: Budesonide Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Budesonide was given by intranasal administration (25 l each time) on Days 17,18,19, and 20 ( Figure 1). On Days 19 and 20, budesonide was given 1 h before intranasal OVA challenge.…”
Section: Budesonide Treatmentmentioning
confidence: 99%
“…There is now evidence to suggest that IL-5 plays a prominent role in eosinophil recruitment, and a unique role in terminal differentiation and maturation of eosinophil lineage-committed progenitors (15,16). Clinically, it has been demonstrated that there are significant correlations between T cell activation, increased concentration of IL-5 in serum and bronchoalveolar lavage fluids (BALF), and asthma severity (17)(18)(19). IL-5 has thus been considered as a potentially important eosinopoietic signal between lung and bone marrow in asthma (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have shown elevated concentrations of the soluble form of CD25 (sCD25), released by activated T cells,11 12 and ECP13 in the serum of asthmatic adults and children compared with controls. Some of these studies have suggested a correlation between the concentrations of these products and disease severity, highlighting the possible role of these markers as simple objective measures to monitor disease activity and response to treatment.…”
mentioning
confidence: 99%
“…It also increases the migration of eosinophils to local lesions [15,21], maintains the survival of mature eosinophils by inhibiting apoptosis [21,22], and directly induces eosinophil degranulation and superoxide production [4,5] in humans. It is reported that serum IL-5 levels are significantly higher in human patients with asthma, and a significant positive correlation was found between the serum concentration of IL-5 and that of eosinophil cationic protein [9]. Administration of an anti-IL-5 antibody blocked eosinophilia more effectively than anti-IL-3 or anti-GM-CSF antibody in a mouse model of allergy [17].…”
mentioning
confidence: 99%